Advancing Anesthesia Care and Challenges by Artificial Intelligence: A Prospective Study based on Systematic Review and Meta-Analysis - Mostafa Ahmed Abdellah Ahmed; Attiya Razzaq; Amna Batool; Shaheer Nayyar; Mahmood Ahmad Zahid; Muhammad Hussain (Pakistan Journal of Medicine and Dentistry)
Background: AI technologies remain essential in modern perioperative care, where they improve clinical decision outcomes and delivery of anesthesia. Health professionals need additional validation testing to determine the practical implementation of these systems for regular medical practice. This study aimed to evaluate the clinical effectiveness and diagnostic accuracy of AI-based tools in anesthesia and perioperative care.